Source book on district disaster management / edited by P. Michael Vetha Siromony - Siromony, Michael Vetha (ed.) (Mussoorie, 2000)
Indio is a disaster prone country. In view of its sub tropical location, long coast line and the tectonic history, India is vulnerable to major E natural hazards, such as, Earthquakes, Cyclones, Floods and Droughts. Man I made disasters like Fires, Bomb blasts, Building Collapses, Road Accidents, Boot Capsizes and Dam Bursts too are common.
Keywords: Disaster management